2019
DOI: 10.14260/jemds/2019/438
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hypospadias in a Tertiary Care Hospital in Coastal Andhra Pradesh

Abstract: BACKGROUND Hypospadias is the commonest paediatric urological condition with an incidence of 1 in 125 male children. The condition can be easily recognized by the attending neonatologist/ paediatrician in the neonatal period. The ideal time for urethral reconstruction is at one year of age and all the staged repairs are to be completed by the time the child goes to school. METHODS We wanted to study the clinical features and outcome of hypospadias cases in the paediatric age group. Children with hypospadias in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…Urethrocutaneous fistula was 4.0% in Snodgrass surgical technique, where as 8.0% in Bracka's technique. The prevalence of fistula in this study was in line with the findings reported by Hashish et al and Poondla et al (7,15) Whereas, studies by Shah et. al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Urethrocutaneous fistula was 4.0% in Snodgrass surgical technique, where as 8.0% in Bracka's technique. The prevalence of fistula in this study was in line with the findings reported by Hashish et al and Poondla et al (7,15) Whereas, studies by Shah et. al.…”
Section: Discussionsupporting
confidence: 92%
“…On pre-operative examination, 52% patients had coronal meatal position, 21% had sub-coronal and 18% had distal penile. While over two-third (75.0%) don't underwent circumcision these is similar to the results reported by Poondla et al and Hashish MS et al (7,15) In every surgery, the duration of the surgery is an important component that may vary from technique to technique and expertise to expertise of surgeon. As far as concern with the duration of surgery, there was a statistically significant difference (p<0.05) was observed between the two used surgical techniques, with the longer duration (79.7±15.6 minutes) in Snodgrass approach compared with the Bracka's technique (66.1±7.23 minutes).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation